Lithium-sulfur battery positive electrode material, preparation method thereof and positive electrode sheet

CN122950397APending Publication Date: 2026-10-20龙子湖新能源实验室 +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510463476.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-14
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0003]针对锂硫电池正极材料导电性及循环稳定性差的技术问题,本发明提出一种锂硫电池正极材料及其制备方法、正极片,本发明中硫碘化合物具备良好的导电性,可以有效提高正极材料电子电导率,有效抑制穿梭效应及提升硫利用率

Benefits of technology

[0017]所述正极材料、导电剂及粘结剂的质量占比为(75.5-90.5):(5-20):(4.5)。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005357826180000011
    Figure HDA0005357826180000011
  • Figure HDA0005357826180000012
    Figure HDA0005357826180000012
  • Figure HDA0005357826180000013
    Figure HDA0005357826180000013
Patent Text Reader

Abstract

This invention proposes a lithium-sulfur battery cathode material and its preparation method, as well as a cathode sheet, belonging to the field of lithium-sulfur battery technology, to solve the technical problems of poor conductivity and cycle stability of lithium-sulfur battery cathode materials. The preparation method of the lithium-sulfur battery cathode material of this invention includes the following steps: (1) mixing elemental sulfur and elemental iodine and ball milling, followed by heat treatment to obtain a sulfur-iodine compound; (2) mixing elemental sulfur, polyacrylonitrile, and conductive particles, followed by calcination to obtain sulfurized polyacrylonitrile; (3) mixing the sulfur-iodine compound and sulfurized polyacrylonitrile and ball milling to obtain the cathode material. Then, it is homogenized with a binder and a conductive agent to obtain a slurry, which is finally coated onto the surface of a current collector and dried to obtain the cathode sheet. The high electronic conductivity of the sulfur-iodine compound in the cathode sheet of this invention can greatly alleviate the shuttle effect, enhance structural stability, and ultimately improve capacity utilization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of lithium-sulfur batteries, and particularly relates to a cathode material. Background Technology

[0002] Lithium-sulfur (Li-S) batteries are considered a core candidate technology for next-generation high-energy-density energy storage systems due to their theoretical energy density of up to 2600 Wh / kg (calculated with sulfur cathode and lithium anode), abundant sulfur resources, low cost, and environmental friendliness. However, elemental sulfur (S8) has inherent defects as a cathode active material, such as extremely low conductivity. Elemental sulfur and its discharge product, lithium sulfide (Li2S), are both electronic and ionic insulators, leading to low utilization of active material (typically less than 50%) and slow reaction kinetics; volume expansion, with sulfur undergoing approximately 80% volume change during charge and discharge, causing electrode structure rupture, active material detachment from the current collector, and rapid capacity decay; and the shuttle effect of polysulfides, with intermediate products including soluble polysulfides (Li2S). n (4≤n≤8) dissolves in the electrolyte and migrates to the negative electrode, undergoing irreversible side reactions with lithium metal, resulting in the loss of active sulfur, reduced coulombic efficiency, and shortened cycle life. These problems collectively and severely restrict the practical application of lithium-sulfur batteries. To overcome these issues, some researchers have focused on the design of sulfur-host materials, mainly including carbon-based composite materials, polar material modification, and the use of sulfurized polyacrylonitrile (SPAN) to address the inherent drawbacks of lithium-sulfur batteries. For example, patent publication number CN115304797A discloses a sulfurized polyacrylonitrile material and its lithium-sulfur battery cathode and lithium-sulfur battery. This patent describes a sulfurized polyacrylonitrile material formed by heating a mixture of polyacrylonitrile and sulfur powder, which has a coulombic efficiency close to 100% and an extremely low self-discharge rate. As a sulfur-containing cathode material, sulfurized polyacrylonitrile can exist stably in the electrolyte and participate in the lithium-ion cycle, without the "shuttle effect" of lithium-sulfur batteries. Using sulfurized polyacrylonitrile (SPAN) as the cathode material in lithium-sulfur batteries can maintain the conductivity of lithium-sulfur batteries, alleviate volume expansion during charge and discharge, and improve the cycle performance of lithium-sulfur batteries. However, SPAN still suffers from insufficient intrinsic conductivity and irreversible capacity loss in the first cycle. Therefore, it is necessary to develop new technical strategies to improve the conductivity and cycle stability of cathode materials, ultimately promoting the development of cathode materials for lithium-sulfur batteries. Summary of the Invention

[0003] To address the technical problems of poor conductivity and cycle stability of lithium-sulfur battery cathode materials, this invention proposes a lithium-sulfur battery cathode material, its preparation method, and cathode sheet. In this invention, the sulfur-iodine compound has good conductivity, which can effectively improve the electronic conductivity of the cathode material, effectively suppress the shuttle effect, and improve sulfur utilization.

[0004] To achieve the above objectives, the technical solution of the present invention is implemented as follows:

[0005] A method for preparing a lithium-sulfur battery cathode material includes the following steps:

[0006] (1) Mix elemental sulfur and elemental iodine, ball mill, and then heat treat to obtain sulfur-iodine compound;

[0007] (2) Mix elemental sulfur, polyacrylonitrile and conductive particles, and then calcine them to obtain sulfurized polyacrylonitrile.

[0008] (3) The positive electrode material is obtained by ball milling a mixture of sulfur-iodine compound and sulfurized polyacrylonitrile.

[0009] The molar ratio of sulfur to iodine is 8–10:1.

[0010] The heat treatment is performed at a temperature of 70–90°C for 2–5 hours.

[0011] The conductive particles are multi-walled carbon nanotubes or conductive carbon black.

[0012] The mass ratio of elemental sulfur to polyacrylonitrile is 6-8:4-2.

[0013] According to the method for preparing the lithium-sulfur battery cathode material according to claim 5, the amount of conductive particles added is 1 to 5% of the sum of the mass of elemental sulfur and polyacrylonitrile.

[0014] The method for preparing the lithium-sulfur battery cathode material according to claim 7 is characterized in that the calcination temperature is 300-380°C and the time is 8-12 hours.

[0015] The method for preparing the lithium-sulfur battery cathode material according to claim 1 is characterized in that the mass ratio of the sulfur-iodine compound to the sulfurized polyacrylonitrile is 1-4:4-1.

[0016] A positive electrode sheet for a lithium-sulfur battery is obtained by mixing a lithium-sulfur battery positive electrode material, a conductive agent, and a binder to prepare a slurry, and then coating the slurry onto a current collector.

[0017] The mass ratio of the positive electrode material, conductive agent and binder is (75.5-90.5):(5-20):(4.5).

[0018] The coating thickness on the current collector is 100-300 μm.

[0019] The adhesive is a mixture of polyacrylic acid and carboxymethyl cellulose or nitrogen-methylpyrrolidone.

[0020] The conductive agent is carbon nanotubes.

[0021] The beneficial effects of the present invention.

[0022] (1) The electrical conductivity of sulfur-iodine compounds is increased by approximately 11 orders of magnitude compared to sulfur, indicating that iodine (I) acts as a redox reactive substance, accelerating the conversion kinetics of sulfur. Elemental iodine and triiodine anion (I3) - It can reversibly participate in the reaction during charging and discharging, reducing the reaction energy barrier and improving sulfur utilization.

[0023] (2) The introduction of iodine can optimize the electronic structure of SPAN, improve the intrinsic conductivity of the composite material, reduce the dependence on carbon additives, and thus maintain high sulfur loading. The interaction between iodine and the SPAN skeleton can inhibit sulfur loss and structural collapse. Combined with the inherent solid-phase transformation mechanism of SPAN, it can further inhibit volume expansion and polysulfide shuttle.

[0024] (3) Sulfur-iodine compounds can improve conductivity and effectively inhibit the dissolution of polysulfides, while sulfurized polyacrylonitrile can enhance the structural stability of the cathode material and improve the cycle performance of the battery. Through the design of this composite material, the energy density, power density and cycle life of lithium-sulfur batteries can be effectively improved, providing new ideas for the research and development of next-generation high-performance batteries. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1 The images are SEM images of the sulfur-iodine compounds prepared in Example 1, (a) 2000x magnification; (b) 15000x magnification.

[0027] Figure 2 The images are SEM images of the cathode material obtained by mixing sulfur-iodine compound and sulfurized polyacrylonitrile in Example 1, (a) 2000x magnification; (b) 20000x magnification.

[0028] Figure 3 This is a schematic diagram of the positive electrode sheet in Example 1, where 1 is the positive electrode material; 2 is the conductive agent and binder coating; and 3 is the current collector.

[0029] Figure 4 The S2p and I3d spectra of the cathode material in Example 1 are shown.

[0030] Figure 5 The diagram shows the cyclic performance of Example 1, Comparative Example 1, and Comparative Example 2. Detailed Implementation

[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] Example 1

[0033] A lithium-sulfur battery cathode material, the preparation method includes the following steps:

[0034] Elemental sulfur and elemental iodine were weighed and ground at a stoichiometric ratio of 9:1 for 15 min. Then, they were added to a ball mill jar at a mass ratio of 1:10 with zirconium beads and milled at 300 r / min for 30 min to obtain a sulfur-iodine mixture. The mixture was then heated to 80℃ in an oven and held for 3 h, followed by natural cooling to obtain a sulfur-iodine compound. Subsequently, elemental sulfur and polyacrylonitrile were mixed at a mass ratio of 4:1, with 1 wt% carbon nanotubes added. The mixture was then heated to 350℃ in a tube furnace and cooled to obtain vulcanized polyacrylonitrile. Finally, the sulfur-iodine compound and vulcanized polyacrylonitrile were placed in a ball mill jar at a mass ratio of 1:1 (material-to-bead ratio 1:10), milled at 500 r / min for a total time of 8 h to obtain the cathode material. The SEM and XPS results of the prepared sulfur-iodine compound are shown below. Figure 1 and Figure 4 The SEM image of the iodine compound and the vulcanized polyacrylonitrile composite material is shown below. Figure 2 As shown.

[0035] The above materials are used to prepare a positive electrode sheet, with the structure as follows: Figure 3 As shown, from bottom to top, the components are: positive electrode material 1, conductive agent and binder coating 2, and current collector 3. The preparation method includes the following steps:

[0036] The positive electrode material, carbon nanotubes, and carboxymethyl cellulose were uniformly mixed in distilled water at a mass ratio of 37.75:37.75:20:4.5 to form a slurry, which was then coated onto the surface of aluminum foil and dried to form a lithium-sulfur battery positive electrode sheet with a coating thickness of 200 μm. Then, a lithium metal sheet was used as the negative electrode, and a 1.5 M LiTFSI / DME-TTE organic lithium salt solution was used as the electrolyte. Long-life cycle tests were conducted at 0.5 C.

[0037] Comparative Example 1

[0038] The sulfur-iodine compound, carbon nanotubes, and carboxymethyl cellulose prepared in Example 1 were uniformly mixed in distilled water at a mass ratio of 37.75:37.75:20:4.5 to form a slurry, which was then coated onto the surface of aluminum foil and dried to form a lithium-sulfur battery positive electrode with a coating thickness of 200 μm. A long-life cycle test was then conducted at 0.5C using a lithium metal sheet as the negative electrode and a 1.5 M LiTFSI / DME-TTE organic lithium salt solution as the electrolyte.

[0039] Comparative Example 2

[0040] The sulfurized polyacrylonitrile, conductive agent, and carboxymethyl cellulose prepared in Example 1 were uniformly mixed in distilled water at a mass ratio of 37.75:37.75:20:4.5 to form a slurry. This slurry was then coated onto an aluminum foil surface and dried to form a lithium-sulfur battery positive electrode with a coating thickness of 200 μm. This electrode was then used as the working electrode, with a lithium metal sheet as the counter electrode, and a 1.5 M LiTFSI / DME-TTE organic lithium salt solution as the electrolyte. Long-life cycle testing was conducted at 0.5 C. The long-life cycle performance is shown in the figure below. Figure 5 As shown, Example 1 exhibited the highest initial specific capacity and more stable cycling performance thereafter, while Comparative Examples 1 and 2 showed instability in terms of capacity utilization and cycling performance.

[0041] Example 2

[0042] A lithium-sulfur battery cathode material, the preparation method includes the following steps:

[0043] Elemental sulfur and elemental iodine were weighed and ground at a stoichiometric ratio of 8:1 for 15 minutes. Then, they were added to a ball mill jar at a mass ratio of 1:10 with zirconium beads and milled at 300 r / min for 30 minutes to obtain a sulfur-iodine mixture. This mixture was then heated to 80℃ in an oven and held for 3 hours, followed by natural cooling to obtain a sulfur-iodine compound. Subsequently, elemental sulfur and polyacrylonitrile were mixed at a mass ratio of 4:1, with an additional 1 wt% of carbon nanotubes (the sum of the masses of elemental sulfur and polyacrylonitrile) added. This mixture was then placed in a tube furnace and heated to 350℃, held for 8 hours, and then cooled to obtain vulcanized polyacrylonitrile. Finally, the sulfur-iodine compound and vulcanized polyacrylonitrile were placed in a ball mill jar at a mass ratio of 1:1 (material-to-ball ratio 1:10), milled at 500 r / min for a total time of 8 hours to obtain the cathode material.

[0044] Example 3

[0045] A lithium-sulfur battery cathode material, the preparation method includes the following steps:

[0046] Elemental sulfur and elemental iodine were weighed and ground at a stoichiometric ratio of 9:1 for 15 minutes. Then, they were added to a ball mill jar at a mass ratio of 1:10 with zirconium beads and milled at 300 r / min for 30 minutes to obtain a sulfur-iodine mixture. This mixture was then heated to 70°C in an oven and held for 3 hours, followed by natural cooling to obtain a sulfur-iodine compound. Subsequently, elemental sulfur and polyacrylonitrile were mixed at a mass ratio of 4:1, with an additional 1 wt% of carbon nanotubes (the sum of the masses of elemental sulfur and polyacrylonitrile) added. This mixture was then placed in a tube furnace and heated to 350°C, held for 8 hours, and then cooled to obtain vulcanized polyacrylonitrile. Finally, the sulfur-iodine compound and vulcanized polyacrylonitrile were placed in a ball mill jar at a mass ratio of 1:1 (material-to-ball ratio 1:10), milled at 500 r / min for a total time of 8 hours to obtain the cathode material.

[0047] Example 4

[0048] A lithium-sulfur battery cathode material, the preparation method includes the following steps:

[0049] Elemental sulfur and elemental iodine were weighed and ground at a stoichiometric ratio of 9:1 for 15 minutes. Then, they were added to a ball mill jar at a mass ratio of 1:10 with zirconium beads and milled at 300 r / min for 30 minutes to obtain a sulfur-iodine mixture. The mixture was then heated to 80℃ in an oven and held for 2 hours, followed by natural cooling to obtain a sulfur-iodine compound. Subsequently, elemental sulfur and polyacrylonitrile were mixed at a mass ratio of 4:1, with an additional 1 wt% of carbon nanotubes (the sum of the masses of elemental sulfur and polyacrylonitrile) added. The mixture was then placed in a tube furnace and heated to 350℃, held for 8 hours, and then cooled to obtain vulcanized polyacrylonitrile. Finally, the sulfur-iodine compound and vulcanized polyacrylonitrile were placed in a ball mill jar at a mass ratio of 1:1 (material-to-ball ratio 1:10), milled at 500 r / min for a total time of 8 hours to obtain the cathode material.

[0050] Example 5

[0051] A lithium-sulfur battery cathode material, the preparation method includes the following steps:

[0052] Elemental sulfur and elemental iodine were weighed and ground at a stoichiometric ratio of 9:1 for 15 minutes. Then, they were added to a ball mill jar at a mass ratio of 1:10 with zirconium beads and milled at 300 r / min for 30 minutes to obtain a sulfur-iodine mixture. The mixture was then heated to 80℃ in an oven and held for 3 hours, followed by natural cooling to obtain a sulfur-iodine compound. Subsequently, elemental sulfur and polyacrylonitrile were mixed at a mass ratio of 7:3, with an additional 1 wt% of carbon nanotubes (the sum of the masses of elemental sulfur and polyacrylonitrile) added. The mixture was then placed in a tube furnace and heated to 350℃, held for 8 hours, and then cooled to obtain vulcanized polyacrylonitrile. Finally, the sulfur-iodine compound and vulcanized polyacrylonitrile were placed in a ball mill jar at a mass ratio of 1:1 (material-to-ball ratio 1:10), milled at 500 r / min for a total time of 8 hours to obtain the cathode material.

[0053] Example 6

[0054] A lithium-sulfur battery cathode material, the preparation method includes the following steps:

[0055] Elemental sulfur and elemental iodine were weighed and ground at a stoichiometric ratio of 9:1 for 15 minutes. Then, they were added to a ball mill jar at a mass ratio of 1:10 with zirconium beads and milled at 300 r / min for 30 minutes to obtain a sulfur-iodine mixture. This mixture was then heated to 80℃ in an oven and held for 3 hours, followed by natural cooling to obtain a sulfur-iodine compound. Subsequently, elemental sulfur and polyacrylonitrile were mixed at a mass ratio of 4:1, with an additional 2 wt% of carbon nanotubes (the sum of the masses of elemental sulfur and polyacrylonitrile) added. This mixture was then placed in a tube furnace and heated to 350℃, held for 8 hours, and then cooled to obtain vulcanized polyacrylonitrile. Finally, the sulfur-iodine compound and vulcanized polyacrylonitrile were placed in a ball mill jar at a mass ratio of 1:1 (material-to-ball ratio 1:10), milled at 500 r / min for a total time of 8 hours to obtain the cathode material.

[0056] Example 7

[0057] A lithium-sulfur battery cathode material, the preparation method includes the following steps:

[0058] Elemental sulfur and elemental iodine were weighed and ground at a stoichiometric ratio of 9:1 for 15 minutes. Then, they were added to a ball mill jar at a mass ratio of 1:10 with zirconium beads and milled at 300 r / min for 30 minutes to obtain a sulfur-iodine mixture. This mixture was then heated to 80°C in an oven and held for 3 hours, followed by natural cooling to obtain a sulfur-iodine compound. Subsequently, elemental sulfur and polyacrylonitrile were mixed at a mass ratio of 4:1, with an additional 1 wt% of carbon nanotubes (the sum of the masses of elemental sulfur and polyacrylonitrile) added. This mixture was then placed in a tube furnace and heated to 300°C, held for 8 hours, and then cooled to obtain vulcanized polyacrylonitrile. Finally, the sulfur-iodine compound and vulcanized polyacrylonitrile were placed in a ball mill jar at a mass ratio of 1:1 (material-to-ball ratio 1:10), milled at 500 r / min for a total time of 8 hours to obtain the cathode material.

[0059] Example 8

[0060] A lithium-sulfur battery cathode material, the preparation method includes the following steps:

[0061] Elemental sulfur and elemental iodine were weighed and ground at a stoichiometric ratio of 9:1 for 15 minutes. Then, they were added to a ball mill jar at a mass ratio of 1:10 with zirconium beads and milled at 300 r / min for 30 minutes to obtain a sulfur-iodine mixture. The mixture was then heated to 80℃ in an oven and held for 3 hours, followed by natural cooling to obtain a sulfur-iodine compound. Subsequently, elemental sulfur and polyacrylonitrile were mixed at a mass ratio of 4:1, with an additional 1 wt% of carbon nanotubes (the sum of the masses of elemental sulfur and polyacrylonitrile) added. The mixture was then placed in a tube furnace and heated to 350℃, held for 10 hours, and cooled to obtain vulcanized polyacrylonitrile. Finally, the sulfur-iodine compound and vulcanized polyacrylonitrile were placed in a ball mill jar at a mass ratio of 1:1 (material-to-ball ratio 1:10), milled at 500 r / min for a total time of 8 hours to obtain the cathode material.

[0062] Example 9

[0063] A lithium-sulfur battery cathode material, the preparation method includes the following steps:

[0064] Elemental sulfur and elemental iodine were weighed and ground at a stoichiometric ratio of 9:1 for 15 minutes. Then, they were added to a ball mill jar at a mass ratio of 1:10 with zirconium beads and milled at 300 r / min for 30 minutes to obtain a sulfur-iodine mixture. The mixture was then heated to 80℃ in an oven and held for 3 hours, followed by natural cooling to obtain a sulfur-iodine compound. Subsequently, elemental sulfur and polyacrylonitrile were mixed at a mass ratio of 4:1, with an additional 1 wt% of carbon nanotubes (the sum of the masses of elemental sulfur and polyacrylonitrile) added. The mixture was then placed in a tube furnace and heated to 350℃, held for 8 hours, and then cooled to obtain vulcanized polyacrylonitrile. Finally, the sulfur-iodine compound and vulcanized polyacrylonitrile were placed in a ball mill jar at a mass ratio of 4:1 (material-to-ball ratio 1:10), milled at 500 r / min for a total time of 8 hours to obtain the cathode material.

[0065] Example 10

[0066] A lithium-sulfur battery cathode material, the preparation method includes the following steps:

[0067] Elemental sulfur and elemental iodine were weighed and ground at a stoichiometric ratio of 10:1 for 15 min. Then, they were added to a ball mill jar at a mass ratio of 1:10 with zirconium beads and milled at 300 r / min for 30 min to obtain a sulfur-iodine mixture. The mixture was then heated to 90℃ in an oven and held for 2 h, followed by natural cooling to obtain a sulfur-iodine compound. Subsequently, elemental sulfur and polyacrylonitrile were mixed at a mass ratio of 2:1, with an additional 1 wt% of carbon nanotubes (the sum of the masses of elemental sulfur and polyacrylonitrile) added. The mixture was then placed in a tube furnace and heated to 350℃, held for 8 h, and cooled to obtain vulcanized polyacrylonitrile. Finally, the sulfur-iodine compound and vulcanized polyacrylonitrile were placed in a ball mill jar at a mass ratio of 1:2 (material-to-ball ratio 1:10), milled at 500 r / min for a total time of 8 h to obtain the cathode material.

[0068] Example 11

[0069] A lithium-sulfur battery cathode material, the preparation method includes the following steps:

[0070] Elemental sulfur and elemental iodine were weighed and ground at a stoichiometric ratio of 9:1 for 15 minutes. Then, they were added to a ball mill jar at a mass ratio of 1:10 with zirconium beads and milled at 300 r / min for 30 minutes to obtain a sulfur-iodine mixture. This mixture was then heated to 70°C in an oven and held for 5 hours, followed by natural cooling to obtain a sulfur-iodine compound. Subsequently, elemental sulfur and polyacrylonitrile were mixed at a mass ratio of 3:1, with an additional 5 wt% of carbon nanotubes (the sum of the masses of elemental sulfur and polyacrylonitrile) added. This mixture was then placed in a tube furnace and heated to 380°C, held for 8 hours, and then cooled to obtain vulcanized polyacrylonitrile. Finally, the sulfur-iodine compound and vulcanized polyacrylonitrile were placed in a ball mill jar at a mass ratio of 1:4 (material-to-ball ratio 1:10), milled at 500 r / min for a total time of 8 hours to obtain the cathode material.

[0071] Example 12

[0072] A lithium-sulfur battery cathode material, the preparation method includes the following steps:

[0073] Elemental sulfur and elemental iodine were weighed and ground at a stoichiometric ratio of 9:1 for 15 minutes. Then, they were added to a ball mill jar at a mass ratio of 1:10 with zirconium beads and milled at 300 r / min for 30 minutes to obtain a sulfur-iodine mixture. The mixture was then heated to 80℃ in an oven and held for 3 hours, followed by natural cooling to obtain a sulfur-iodine compound. Subsequently, elemental sulfur and polyacrylonitrile were mixed at a mass ratio of 2:1, with an additional 2 wt% superP (the sum of the masses of elemental sulfur and polyacrylonitrile) added. The mixture was then placed in a tube furnace and heated to 350℃, held for 12 hours, and then cooled to obtain vulcanized polyacrylonitrile. Finally, the sulfur-iodine compound and vulcanized polyacrylonitrile were placed in a ball mill jar at a mass ratio of 2:1 (material-to-bead ratio 1:10), milled at 500 r / min for a total time of 8 hours to obtain the cathode material.

[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a lithium-sulfur battery cathode material, characterized in that, Includes the following steps: (1) Mix elemental sulfur and elemental iodine, ball mill, and then heat treat to obtain sulfur-iodine compound; (2) Mix elemental sulfur, polyacrylonitrile and conductive particles, and then calcine them to obtain sulfurized polyacrylonitrile. (3) The positive electrode material is obtained by ball milling a mixture of sulfur-iodine compound and sulfurized polyacrylonitrile.

2. The method for preparing the lithium-sulfur battery cathode material according to claim 1, characterized in that, The molar ratio of sulfur to iodine is 8–10:

1.

3. The method for preparing the lithium-sulfur battery cathode material according to claim 2, characterized in that, The heat treatment is performed at a temperature of 70–90°C for 2–5 hours.

4. The method for preparing the lithium-sulfur battery cathode material according to any one of claims 1-3, characterized in that, The conductive particles are multi-walled carbon nanotubes or conductive carbon black.

5. The method for preparing the lithium-sulfur battery cathode material according to claim 4, characterized in that, The mass ratio of elemental sulfur to polyacrylonitrile is 6-8:4-2.

6. The method for preparing the lithium-sulfur battery cathode material according to claim 5, characterized in that, The amount of conductive particles added is 1 to 5% of the sum of the mass of elemental sulfur and polyacrylonitrile.

7. The method for preparing the lithium-sulfur battery cathode material according to claim 6, characterized in that, The calcination temperature is 300–380℃, and the time is 8–12 hours.

8. The method for preparing the lithium-sulfur battery cathode material according to claim 1, characterized in that, The mass ratio of the sulfur-iodine compound to the sulfurized polyacrylonitrile is 1-4:4-1.

9. The lithium-sulfur battery cathode material prepared by the method according to any one of claims 1-8.

10. A positive electrode sheet for a lithium-sulfur battery, characterized in that, A slurry prepared by mixing the lithium-sulfur battery cathode material, conductive agent, and binder as described in claim 9 is coated onto a current collector.

Citation Information

Patent Citations

  • Vulcanized polyacrylonitrile material, lithium-sulfur battery positive electrode thereof and lithium-sulfur battery

    CN115304797A